Two-step process for disassembly mechanism of proteasome α7 homo-tetradecamer by α6 revealed by high-speed atomic force microscopy - Kozai, Toshiya (Sci Rep, 2017)
The 20S proteasome is a core particle of the eukaryotic proteasome responsible for proteolysis and is composed of layered α and β hetero-heptameric rings. The α7 subunit, which is one of components of the α ring, is known to self-assemble into a double-ringed homo-tetradecamer composed of two layers of the α7 heptameric ring. The α7 tetradecamer is known to disassemble upon the addition of α6 subunit, producing a 1:7 hetero-octameric α6-α7 complex. However, the detailed disassembly mechanism remains unclear. Here, we applied high-speed atomic force microscopy (HS-AFM) to dissect the disassembly process of the α7 double ring caused by interaction with the α6. HS-AFM movies clearly demonstrated two different modes of interaction in which the α6 monomer initially cracks at the interface between the stacked two α7 single rings and the subsequent intercalation of the α6 monomer in the open pore of the α7 single ring blocks the re-association of the single rings into the double ring. This result provides a mechanistic insight about the disassembly process of non-native homo-oligomers formed by proteasome components which is crucial for the initial process for assembly of 20S proteasome.